THE IMPLEMENTATION OF NUMBERED HEAD TOGETHER MODEL TO IMPROVE STUDENTS’ ACCOUNTING LEARNING ACTIVITY - Frank Aligarh; Annisa Ratna Sari (Jurnal Pendidikan Akuntansi Indonesia, 2014)
This study is categorized as a classroom action research that aims to improve the Accounting Learning Activities of the students of class XI Accounting 1 SMK N 1 Depok Sleman academic year 2013/ 2014. This study is a collaborative research which is conducted in two cycles using the two methods of data collection which are observation and questionnaire. The data is first collected and then analyzed by the analysis of qualitative data through two stages, namely the presenting the data and drawing the conclusions. Qualitative analysis is then fitted with a descriptive analysis using quantitative percentage to calculate the score Accounting Learning Activities. Based on the results of the study, it can be concluded that the implementation of Cooperative Learning Model using Numbered Head Together type can improve Accounting Learning Activities of the students of Class XI Accounting Skills Competency SMK N 1 Depok Sleman Academic Year 2013/ 2014. It is evidenced by an increasing score on Accounting Learning Activities of the students’ of class XI Accounting 1. It increased from 67.30% in the first cycle to 83.04% in the second cycle. It also shows that the average score of students’ Accounting Learning Activities in the second cycle has reached the expectation score, i.e. 75%.   Keywords: Cooperative Learning of NHT type, Activity, Accounting Learning Activity